The Effectiveness of Otanaha Compliant Operations in Preventing Traffic Violations - Cipto Kai (Universitas Negeri Gorontalo, 2023)
Abstract: Purposeful researchknow ethe effectiveness of the implementation of Otanaha compliance operations in preventing traffic violations in the city of Gorontalo and what are the inhibiting factors for the implementation of Otanaha compliance operations in preventing traffic violations in the city of Gorontalo. This type of research uses empirical research methods carried out with a qualitative approach to primary and secondary data. The research was located at the Gorontalo City Police, the data used in this study were obtained using interview techniques. The results of this study can be concluded that The effectiveness of the implementation of the Otanaha Obedience Operation in Preventing Traffic Violations in the City of Gorontalo, namely: Lack of awareness from the public,The weather factor is not supportive, the community is not orderly towards traffic order, there is a lack of awareness of road users. The inhibiting factors for the implementation of Otanaha compliance operations in preventing traffic violations in the city of Gorontalo are: Helping the community in safety and public order in driving on the road, Reducing the number of road accidents, Increasing legal awareness indriving people,Socializing and notification of operations to the community.